DISLOCATION OF ISLAMIC SCIENTIFIC TRADITION THROUGH DIGITAL PUBLIC SPHERE: NETNOGRAPHIC ANALYSIS ON THE DISCOURSE OF AHL AL-SUNNAH WA AL-JAMA’A BETWEEN TRADITIONALIST AND MODERNIST MUSLIMS - Dhuhri, Saifuddin; Bhakti, Sufri Eka; Kamaruzzaman, Kamaruzzaman; Fauziyah, Nurul Khansa; Wahyudi, Rizqi (Islam Futura, 2025)
On how digital public sphere distort traditional Islamic public sphere, many scholars are convinced that media's work is inextricably linked with producing false consciousness, in which its audiences' opinions are stirred and engineered for Ideological entrenchment. It is a consensus among scholars that media has the effectivity for the propaganda tools, while significant current media theories concern the role of media in favour of the power interest through the mechanism of algorigma; e.g., Echo chambers and filter bubbles. Based on netnographic data on Aswaja discourse, this paper attempts to unearth the dislocation of Islamic scientific tradition through digital public sphere. This paper argues that digital public sphere has played a significant role in disrupted the traditional Islamic scholarly tradition by instrumentalizing religious discourse to maintain hegemony over minority groups. This paper has an important contribution to understanding the mode of piety and religious practices used for cultural hegemony and the ways media plays its role in constructing and remaking the meaning of religious concepts and piety.